Clinical presentation and outcome of ectopic pregnancy - Chundakkadan, Mohammed Sidhiq; K., Chandramathy; Selvest, Neethu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: An ectopic pregnancy is defined as blastomere implants anywhere other than the endometrial lining of the uterine cavity. The incidence was around 1-1.5%. Commonest site in fallopian tube (95%). Even the incidence was small, it accounted for 3% of the pregnancy related deaths. The objective of this study was to evaluate the clinical presentation of various types of ectopic pregnancy, any risk factors, various types of management and the outcome. Methods: This was a prospective COHORT study of 102 ectopic patients admitted at government medical college, Kozhikode during 18 November 2020 to 17 August 2021 with various clinical manifestations. Depends on clinical features, USG findings and HCG estimation, patients were treated by expectant, medical and surgical management. Patients followed up for 2 weeks after discharge. Results: 102 cases were admitted in study period. 98 cases were tubal ectopic. 69.6% with history of various risk factors. Commonest age group was 26-35 years. 70.6% were multiparous. HCG <5000 responded very well to medical management (92.8% success rate). Conclusions: Most common ectopic pregnancy is tubal ectopic and commonly associated with various risk factors. Triad of symptoms will be present in most cases. Early antenatal visit will reduce the number of ruptured ectopic. Careful selection of cases by HCG value and size of ectopic will give excellent result.